Sistem Pengambilan Keputusan Kelayakan Pemberian Kredit Rumah Bersubsidi Menggunakan Fuzzy Sugeno - Silvilestari Silvilestari (STMIK Budi Darma, 2022)
Subsidized housing is a government program to meet the increasing housing needs. This subsidized program is specifically given to people who do not have their own place to live. The problem in this study is that it is difficult to determine who is entitled to receive subsidized housing assistance. The purpose of this study is to facilitate the housing provider selectors in accordance with predetermined criteria. The settlement of this case uses the Decision-Making System method using the concept of Fuzzy Logic. Characteristics and concepts of a Decision-Making System is a process of selecting an alternative action taken to obtain a goal to solve problems in achieving goals in taking a decision. The concept used is the Sugeno method by going through four stages, namely Fuzzification, inference engine, the implication function, and fuzzification by taking the largest x value (Max) with the AND operator process. The final result of determining the feasibility of providing subsidized housing with a value of X, 14,63,100,130 produces output 1 with the decision accepted